Efektivitas layanan bimbingan kelompok dalam meningkatkan disiplin belajar peserta didik - Asy Syauqi, Rahmat Fajri; Suhaili, Neviyarni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study aims to develop a service effectiveness model to improve student learning discipline through group guidance. This research is a quantitative research with a quasi-experimental research method. The quasi-experimental design used is Time series. This research design uses only one group with a total of 10 students with using random sampling technique. The results of research on the effectiveness of group guidance services in improving student learning discipline at SMP N 30 Padang. The data obtained in this research process is the result of the pretest and posttest related to the learning discipline of students, so that the data can be described clearly. The process of analyzing pretest and posttest data using the Wilcoxon'n test. Before being given the group guidance treatment, the average student learning discipline was 77.9% and was dominated by students who were in the low category, the results were obtained from the pretest. Furthermore, based on the results of the posttest and after being given treatment with group guidance services, the average student learning discipline increased to 101%. It can be concluded that the learning discipline of students is increasing and is in the high category.